2003
DOI: 10.1242/jcs.00620
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of NO-sensitive guanylyl cyclase subunits during the development of rat cerebellar granule cells: regulation viaN-methyl-D-aspartate receptors

Abstract: In primary cultures of rat cerebellar granule cells with a functional network of glutamatergic neurons, the expression pattern of the different subunits of nitric-oxide (NO)-sensitive guanylyl cyclase changes during cell differentiation. These cells express the α1,α 2 and β1 subunits of NO-sensitive guanylyl cyclase and synthesize cyclic guanosine monophosphate (cGMP) in response to exogenous or endogenous nitric oxide. In this study, we determined the protein content of the α1 and β1 subunits and quantified α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
40
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Although this experimental approach does not accurately define the location of sGC, these results indicate that active sGC is present in these presynaptic boutons, consistent with the presence of this enzyme in presynaptic terminals and close to the active zone. 11,12,30 The presence of sGC in neuronal processes and in synaptic boutons would also explain its increased expression during development 5 and its importance in regulating different steps of neuronal development.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although this experimental approach does not accurately define the location of sGC, these results indicate that active sGC is present in these presynaptic boutons, consistent with the presence of this enzyme in presynaptic terminals and close to the active zone. 11,12,30 The presence of sGC in neuronal processes and in synaptic boutons would also explain its increased expression during development 5 and its importance in regulating different steps of neuronal development.…”
Section: Discussionmentioning
confidence: 99%
“…33 In addition, GAP-43 mRNA expression is controlled by glutamatergic NMDA receptors, 34 and the formation of NO and cGMP is one consequence of NMDA receptor stimulation. 5,35 We previously demonstrated that NMDA receptor stimulation regulates the stability of different mRNAs via the NO/cGMP pathway, altering the levels of the AUF1 proteins that bind to and destabilize them. 23 Such a process might be active in this paradigm as GAP-43 mRNA has a long 3 0 UTR bearing specific determinant pyrimidinerich sequences that AUF1 can bind to, thereby destabilizing this mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations